Efek Ekstrak Bawang Putih (Allium sativum L.) dalam Menekan Pertumbuhan Bakteri Salmonella typhi secara In vitro - Taufan, Wa Ode Sri Apriani; Idrus, Hasta Handayani; Nurmadilla, Nesyana; Sodiqah, Yani; Muchtar, Amrizal (Rumah Sakit Ibnu Sina, Makassar, 2024)
Salmonella typhi is a Gram-negative bacterium that has no spores, moves with peritrichic flagellum, is facultative intracellular and facultative anaerobic. Garlic (Allium sativum) has been known for a long time to be used as a seasoning and medicine. The antibacterial activity of garlic can control pathogenic bacteria, both gram-negative and positive. To determine the effectiveness of Salmonella typhi bacteria growth given garlic extract (Allium sativum). This research is a true experiment post test using disc diffusion method. The higher the concentration of garlic extract (Allium sativum), the greater the inhibition zone obtained. The highest concentration of 100% garlic extract against Salmonella typhi bacteria has an inhibition zone of 14.4 mm with sensitive interpretation. Garlic extract (Allium sativum) has antibacterial effectiveness against the growth of Salmonella typhi bacteria